A sociological study of menstrual hygiene management in schools in the Makana District, Eastern Cape, South Africa - Bloem, Sharon Gretchen (Rhodes University, Faculty of Humanities, Department of Sociology)
Appropriate menstrual hygiene management is affected by taboos and secrecy surrounding menstruation. Inadequate information and knowledge about menstruation and lack of resources for managing menstruation hygienically have impacted adolescent girls on a psychosocial and physical level. Consequently, the dignity of schoolgirls during the onset of menstruation through puberty and adolescent phases is jeopardised. It is therefore imperative to understand the normal physiological changes that school-going children from Grades 6 to 12 undergo and acknowledge how these changes affect their education within the school environment. In the Makana district, Eastern Cape, South Africa, the topic of menstrual hygiene management is under-researched at schools and, therefore, this research explores school educators' perceptions of menstrual hygiene management at primary, secondary and private schools in this area. Schools have a responsibility to create a safe environment for learners' education, which includes the topic of menstruation without discriminating against or labelling menstruating girls. This research found that the topic of menstruation is only discussed in Life Science and Life Orientation subjects and only covers the physiological changes of the body. These subjects, however, exclude the topic of menstrual hygiene management. This study found that several schools in the Makana district are not adequately equipped to provide for the needs of menstruating girls and therefore educators need to be prepared to deal with menstruation in the school context. The educators are also required to go for regular training or workshops to equip them to manage menstruation in a school environment. The infrastructure of a school includes water and sanitation which are components of menstrual hygiene management. The infrastructure at the participating public schools was inadequate and therefore impacted on the menstrual hygiene management for the girls. The unavailability of water, the non-existence of a sick room and lack of a waste disposal system at some public schools presented further challenges for menstrual hygiene management. A qualitative research method was applied in this study and a symbolic interactionism approach was used.
Keywords: Schoolgirls Health and hygiene -- South Africa -- Makhanda; Menstruation Social aspects -- South Africa -- Makhanda; Health behavior in adolescence -- South Africa -- Makhanda; Teenage girls Health and hygiene -- South Africa -- Makhanda; Teenage girls Physiology -- South Africa -- Makhanda; Life skills -- South Africa -- Makhanda